Clinical Manifestations of Symptomatic Intracranial Hemorrhage in Term Neonates: 18 Years of Experience in a Medical Center - Mei-C; Chung-Bin Huang; Hsin-Chun Huang; Mei-Yung Chung; Chih-Cheng Chen; Feng-Shun Chen; Pei-Hsin Chao; I-Lun Chen; Mei-; Chieh-An Liu (Elsevier, 2010)
Intracranial hemorrhage (ICH) is an uncommon but important cause of morbidity and mortality in term neonates. We conducted a retrospective analysis of the clinical characteristics and developmental outcomes of symptomatic ICH in term neonates. Methods: A retrospective chart review was conducted of all term neonates (less than 1 month old) diagnosed with ICH and admitted to the neonatal intensive care unit of Kaohsiung Chang Gung Hospital from December 1991 to December 2008. Demographic characteristics, mode of delivery, laboratory data, clinical presentation, and developmental status were recorded. Results: Data for 24 term neonates (17 boys and 7 girls) with a diagnosis of ICH were collected for analysis. The clinical manifestations of ICH included anemia (13/24, 54%), seizure (11/24, 46%), cyanosis (7/24, 29%), tachypnea (5/24, 21%), fever (1/24, 4%), hypothermia (1/24, 4%), and poor feeding (1/24, 4%). Age at symptom onset ranged from 2 hours to 11 days following birth. The most common type of ICH was subdural hemorrhage. All ICHs resolved, except in one infant, who died from hypoxicischemic encephalopathy at 25 days. Ten children with symptomatic ICH were reported to have normal development, while the remainder (13/23, 57%) showed developmental delays or disabilities. Conclusion: Unexplained anemia, seizure, and cyanosis were the major presenting signs in infants with symptomatic ICH. A diagnosis of ICH should be considered in term neonates who present with one or more of these signs. Although the mortality in term infants with symptomatic ICH was low, more than half